Features of the Control of 12-pulse Compensated Controlled Rectifier - Butova, Olga (My University, 2013)
In this paper an overview of improved EMC controlled rectifiers is presented. In addition, characteristics of design of control systems of parallel 12-pulse compensated controlled rectifiers are identified.